2018
DOI: 10.1111/nph.15039
|View full text |Cite
|
Sign up to set email alerts
|

Mutational studies of the Aux/IAA proteins in Physcomitrella reveal novel insights into their function

Abstract: Summary • The plant hormone auxin regulates many aspects of plant growth and development. Auxin signaling involves hormone perception by the TRANSPORT INHIBITOR RESPONSE/AUXIN F-BOX (TIR1/AFB)–Aux/IAA co-receptor system, and the subsequent degradation of the Aux/IAA transcriptional repressors by the ubiquitin proteasome pathway. This leads to the activation of downstream gene expression and diverse physiological responses. Here, we investigate how the structural elements in the Aux/IAAs determine their functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…The core mechanisms for auxin sensing are conserved in P. patens and M. polymorpha, indicating that they were already in place in the common ancestors of flowering plants and bryophytes (i.e. in the earliest land plants; Prigge et al, 2010;Lavy et al, 2012Eklund et al, 2015;Flores-Sandoval et al, 2015Kato et al, 2015Kato et al, , 2017Plavskin et al, 2016;Mutte et al, 2018;Tao & Estelle, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The core mechanisms for auxin sensing are conserved in P. patens and M. polymorpha, indicating that they were already in place in the common ancestors of flowering plants and bryophytes (i.e. in the earliest land plants; Prigge et al, 2010;Lavy et al, 2012Eklund et al, 2015;Flores-Sandoval et al, 2015Kato et al, 2015Kato et al, , 2017Plavskin et al, 2016;Mutte et al, 2018;Tao & Estelle, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…1b). In addition, point mutations in conserved residues of the DII domains in the PpAux/ IAAs result in stabilized protein versions conferring auxin resistance, just as in Arabidopsis, and a triple knockout of all moss Aux/IAA genes show dramatic phenotypes, indicating a constitutive auxin response which cannot be altered by changes in auxin concentrations (Prigge et al, 2010;Tao & Estelle, 2018). Transcriptome analysis of the triple mutant indicates that most, if not all, auxin-mediated changes on transcription are relayed through the Aux/IAAs, at least in filamentous protonema .…”
Section: Introductionmentioning
confidence: 99%
“…However, expression of nonoligomerizing IAA17 and IAA19 in protoplasts had an intermediate effect on repressive activity of these Aux/IAAs 53 ; expression of nonoligomerizing IAA1a in Physcomitrella had an intermediate effect on IAA1a repressive activity. 58 Further, expression of a stabilized nonoligomerizing IAA14 variant efficiently repressed auxin responses, 57 consistent with IAA14 oligomerization being unnecessary for ARF repression. In addition, Aux/IAA multimerization may be required for efficient recruitment of TPL, as structural studies have shown that binding affinity of the TPL/TPR co-repressor increases in the presence of oligomerized EAR-motif containing repressors.…”
Section: Pb1 Domain-oligomerizationmentioning
confidence: 76%
“…Overexpression of a stabilized IAA16 with mutations disrupting either the basic or acidic face of the PB1 domain results in the loss of repressive activity of IAA16, suggesting that Aux/IAA multimerization is necessary for biological function. However, expression of nonoligomerizing IAA17 and IAA19 in protoplasts had an intermediate effect on repressive activity of these Aux/IAAs; expression of nonoligomerizing IAA1a in Physcomitrella had an intermediate effect on IAA1a repressive activity . Further, expression of a stabilized nonoligomerizing IAA14 variant efficiently repressed auxin responses, consistent with IAA14 oligomerization being unnecessary for ARF repression.…”
Section: Repression Of Auxin‐responsive Gene Expression Through Aux/imentioning
confidence: 78%
“…The authors had previously demonstrated that moss expressing only IAA1a have wild‐type auxin response and morphology (Lavy et al ., ). In the current study, Tao & Estelle perform quantitative structure/function analysis by substituting sequence variants at the IAA1a locus in the sensitized background of an iaa1b iaa2 double mutant. Their approach has made it possible to make definitive statements about a number of features of Aux/IAA function that have been the subject of debate since their initial discovery.…”
mentioning
confidence: 99%